Effect of Cobalt Fillers on Polyurethane Segmentations Investigated by Synchrotron Small Angle X-Ray Scattering - Krit Koyvanich; Chitnarong Sirisathitkul; Supagorn Rugmai (Advances in Materials Science and Engineering)
The segmentation between rigid and rubbery chains in polyurethanes (PUs) influences polymeric properties and implementations. Several models have successfully been proposed to visualize the configuration between the hard segment (HS) and soft segment (SS). For particulate PU composites, the arrangement of HS and SS is more complicated because the fillers tend to disrupt the chain formation and segmentation. In this work, the effect of ferromagnetic cobalt (Co) powders (average diameter 2 μm) on PU synthesized from a reaction between polyether polyol (soft segment) and diphenylmethane-4,4′-diisocyanate (hard segment) was studied with varying loadings (0, 20, 40, and 60 wt.%). The 300 μm thick PU/Co samples were tape-casted and then received heat treatment at 80°C for 180 min. From synchrotron small angle X-ray scattering (SAXS), the plot of the X-ray scattering intensity (I) against the scattering vector (q) exhibited a typical single peak of PU whose intensity was reduced by the increase in the Co loading. Characteristic SAXS peaks in the case of 0-20 wt.% Co agreed well with the scattering by globular hard segment domains according to Zernike-Prins and Percus-Yevick models. The higher Co loadings led to larger deviations from all theoretical models.